2021
DOI: 10.1093/toxres/tfaa098
|View full text |Cite
|
Sign up to set email alerts
|

Lantana camaraethanolic leaves extracts exhibit anti-aging properties inDrosophila melanogaster: survival-rate and life span studies

Abstract: In this article, we aimed to investigate the anti-aging activity of Lantana camara ethanolic leaves-extract in Drosophila melanogaster: survival and longevity (life span). L. camara leaves were collected and washed thoroughly of sand particles, air-dried, ground, and extracted by the maceration method using ethanol as a solvent. Phytochemical screening was carried out. 168-hour LC50 was determined by exposing fruit flies to concentrations ranging from 5 to 5000 mg/10 g diet for 7-days. Twenty-eight-day surviva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…The plants were identified and authenticated by the Department of Plant Science and Biotechnology, University of Jos. The extraction process was carried out according to the method described by Etuh et al [25]. The leaves were washed under running tap water to remove dirt and other particles.…”
Section: Plant Collection Identification and Extractionmentioning
confidence: 99%
See 1 more Smart Citation
“…The plants were identified and authenticated by the Department of Plant Science and Biotechnology, University of Jos. The extraction process was carried out according to the method described by Etuh et al [25]. The leaves were washed under running tap water to remove dirt and other particles.…”
Section: Plant Collection Identification and Extractionmentioning
confidence: 99%
“…A 7-day acute toxicity study (LC 50 ) was carried out following the method described by Etuh et al [25]. This was to determine the concentration of the extract that kills 50 % of the flies in seven ( 7) days [27].…”
Section: Median Lethal Concentration (Lc 50 ) Determinationmentioning
confidence: 99%
“…It has been reported that lantana oil can be used to cure skin itches, as an antiseptic for wounds, and as an external therapy for leprosy and scabies (Aritonang et al, 2019;Liu et al, 2019;Chowdhury et al, 2020;Devi and Khwairakpam, 2020). Lantana extracts are used in folk medicine to treat malignancies, chicken pox, measles, asthma, ulcers, swellings, eczema, tumours, high blood pressure, bilious fevers, catarrhal infections, tetanus, rheumatism, malaria, and atoxy of abdominal viscera (Etuh et al, 2021;Kato-Noguchi and Kurniadie, 2021;Anwar et al, 2021;Delgado-Altamirano et al, 2021). The main task of this study is threefold.…”
Section: Introductionmentioning
confidence: 99%